DAMPAK SOSIAL PEMBANGUNAN TOL CISUMDAWU TERHADAP MASYARAKAT DI KABUPATEN SUMEDANG - Detanty Febrianty; Ellya Susilowati; Atirista Nainggolan (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2022)
Cileunyi-Sumedang-Dawuan Toll Road or Cisumdawu Toll Road is one of the infrastructures that built to facilitate community mobility as a liaison between regions in West Java. The existence of infrastructure construction is inseparable from the social impact felt by the community around the construction area. This study aims to obtain an empirical description of social impact to Sumedang Nitizen from building Cisumdawu Toll Road. The method used in this research is descriptive quantitative method. The sampling technique used is simple random sampling technique with 80 respondents. Data collection techniques used are questionnaire and documentation studies. Validity test using face validity and reliability test using Alpha Cronbach with SPSS’ help. The measuring instrument used in the research questionnaire uses Likert scale. The results of the analysis show that the construction of Cisumdawu Toll Road in Pasigaran Village, Tanjungsari District, Sumedang Regency causes a significant social impact, especially on the needs of the community with the highest score. Then, construction is also affect enough in changes way of community work, recreation and interact socially with a moderate score category. The program that is prepared as an alternative solution to solve the problem is "Reducing the Social Impact of Toll Road Construction through Collaborative Communication" in Pasigaran Village, Tanjungsari District, Sumedang Regency.